Stop it! Relationship between sport expertise and response inhibition in elite athletes - Fleddermann, M. T.; Reichert, L.; Wieland, B.; Zentgraf, K. (Frontiers in Psychology, 2023)
Introduction: The dynamic structure of sport games forces players to make time-sensitive decisions and to initiate actions that may then have to be canceled in response to sudden changes in the game situation. Whether and up to which time already initiated movements can still be inhibited is an important criterion for game performance in elite sport. Research indicates that elite athletes show superior motor inhibition performance compared to recreational athletes. However, no study has examined whether differences also emerge among professional elite athletes themselves. Therefore, this study aimed to investigate whether motor inhibition performance is a differential feature among elite athletes, and whether inhibition performance increases with greater expertise.